Peran Permainan Tradisional terhadap Karakter Kepemimpinan Anak Usia 10-12 Tahun - Chrismantari, Linda; Nugrahanta, Gregorius Ari (Universitas Negeri Makassar, 2023)
The research aimed to develop a traditional game-based leadership character education manual for 10-12 year olds. This research involved 10 teachers from various regions, 10 validators, and 8 children aged 10-12 years. The results of the study showed that 1) the character education handbook was developed using the ADDIE stages; 2) The quality of the manual showed a score of 3.90 (scale 1-4) in the category